2022
DOI: 10.15585/mmwr.mm715152e2
|View full text |Cite
|
Sign up to set email alerts
|

Early Estimates of Bivalent mRNA Vaccine Effectiveness in Preventing COVID-19–Associated Hospitalization Among Immunocompetent Adults Aged ≥65 Years — IVY Network, 18 States, September 8–November 30, 2022

Abstract: this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Monovalent COVID-19 mRNA vaccines, designed against the ancestral strain of SARS-CoV-2, successfully reduced COVID-19related morbidity and mortality in the United States and globally (1,2). However, vaccine effectiveness (VE) against COVID-19associated hospitalization has declined over time, likely related to a combination of factors, including waning immunity and, with the emergence of the Omicron variant and its su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 6 publications
4
81
2
Order By: Relevance
“…Additional studies are needed to evaluate VE against outcomes such as COVID-19–associated severe respiratory illness or death. The IVY Network, an adult inpatient VE network, recently found higher estimated VE in adults aged ≥65 years compared with estimates for those aged ≥18 years included in this analysis ( 6 ). This might reflect differences in population subgroups evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…Additional studies are needed to evaluate VE against outcomes such as COVID-19–associated severe respiratory illness or death. The IVY Network, an adult inpatient VE network, recently found higher estimated VE in adults aged ≥65 years compared with estimates for those aged ≥18 years included in this analysis ( 6 ). This might reflect differences in population subgroups evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…Two recent CDC-led vaccine effectiveness (VE) studies found that the bivalent mRNA vaccine booster provided 42-73% additional protection against COVID-19-associated hospitalization compared with 2 to 4 monovalent COVID-19 vaccine doses during September-November 2022 15, 16 , when BA.5 and BQ.1/BQ.1.1 predominated. In the present study, from the post-third dose monovalent sera to post-fourth dose bivalent vaccine sera, the neutralizing titers increased by 7.1-fold against BA.5 and 12-fold against BQ.1 and BQ.1.1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found that bivalent booster doses produced a robust immunologic response in nursing home residents ( 6 ). Bivalent booster doses have also been shown to provide additional protection against severe outcomes associated with COVID-19, compared with monovalent vaccination alone, including protection against COVID-19–associated emergency department and urgent care visits among adults aged ≥18 years and protection against COVID-19 hospitalization among adults aged ≥65 years ( 7 , 8 ). Public health efforts to sustain up-to-date COVID-19 vaccination status among nursing home residents (including recommended vaccinations and booster doses) are critical to protecting this population.…”
Section: Discussionmentioning
confidence: 99%